Community Education on Eco-Enzyme to Prevent Stunting in Malaka, East Nusa Tenggara - Sudarmaji, Sudarmaji; Adriyani, Retno; Arfiani, Novi Dian; Parmawati, Rita; Wulandari, Prisca Kiki; Nugroho, Agung Murti; Syafei, Arie Dipareza; Assomadi, Abdu Fadli; Febrianto, Arry; Muzakky, Achmad; Ahmad, Imam Safawi (Universitas Pahlawan Tuanku Tambusai, 2025)
Stunting is a serious nutritional problem that requires immediate attention. In Malaka Regency, East Nusa Tenggara Province, the prevalence of stunting remains high due to poor sanitation and ineffective organic waste management. This community service program aims to increase public awareness and skills in utilizing organic waste to produce eco-enzyme and its derivatives, such as eco-enzyme-based liquid soap. The program was conducted from July to November 2025, involving 33 participants representing local government, community leaders, and informal community figures. The activity explained the relationship between sanitation and stunting through discussions and demonstrations on producing eco-enzyme from household organic waste. Evaluation through pre- and post-tests showed a significant increase in participants’ knowledge of sanitation, stunting, and organic waste management. Community-based education on eco-enzyme has proven to support food security and environmental health while contributing to reducing the risk of stunting.